β-Alanine supplementation's improvement of high-intensity game activities in water polo - Brisola, Gabriel Motta Pinheiro; De Souza Malta, Elvis [UNESP]; Santiago, Paulo Roberto Pereira; Vieira, Luiz Henrique Palucci; Zagatto, Alessandro Moura (Human Kinetics, 2018)
Objectives: To investigate whether 4 wk of β-Alanine supplementation improves total distance covered, distance covered and time spent in different speed zones, and sprint numbers during a simulated water polo game. Design: Double-blind, parallel, and placebo controlled. A total of 11 male water polo players participated in the study, divided randomly into 2 homogeneous groups (placebo and β-Alanine). Methods: The participants performed a simulated water polo game before and after the supplementation period (4 wk). They received 4.8 g·d-1 of dextrose or β-Alanine on the first 10 d and 6.4 g·d-1 on the final 18 d. Results: Only the β-Alanine group presented a significant improvement in total sprint numbers compared with the presupplementation moment (PRE = 7.8 [5.2] arbitrary units [a.u.]; POST = 20.2 [7.8] a.u.; P = .002). Furthermore, β-Alanine supplementation presented a likely beneficial effect in improving total distance covered (83%) and total time spent (81%) in speed zone 4 (ie, speed ≥ 1.8 m·s-1). There was no significant interaction effect (group × time) for any variable. Conclusions: Four weeks of β-Alanine supplementation slightly improved sprint numbers and had a likely beneficial effect on improving distance covered and time spent in speed zone 4 in a simulated water polo game.
Keywords: Carnosine; Computational tracking; Dietary supplement; Ergogenic substances; Team sports